Examining Sources of Mathematics Self-Efficacy Beliefs of Senior Secondary School Students - Adeneye Olarewaju A. Awofala (Universitas Pendidikan Indonesia (UPI), 2023)
Except people have confidence that they can produce desired results they have little motivation to act. Self-referent thought plays a significant part in the psychological working of humans. People’s conception of their efficacy is most powerful in their everyday life and the self-efficacy of a person has been recognized as a vital element for executing tasks successfully. While many studies have shown the predictive power of self-efficacy, fewer efforts have examined the sources underlying self-efficacy beliefs. Sources of self-efficacy in mathematics scale was a multi-dimensional construct comprising: mastery experience; vicarious experience; social persuasions; and physiological and affective states. Senior secondary school students had a moderate level of sources of self-efficacy in mathematics. Gender differences in sources of self-efficacy in mathematics among senior secondary school students were significant and in favor of the male students. However, future studies in Nigeria should investigate the confirmatory factor analytic structure of the sources of self-efficacy in mathematics scale to generalize the findings of this study.